Renegotiating Work-Home Boundaries: Reconciliations of Remote Work and School During COVID-19 - Mari Karhu; Jonna Häkkilä; Matilda Kalving; Mari Mäkiranta; Ashley Colley (Nordic Journal of Working Life Studies, 2024)
This article contributes to understanding the radical transformation of everyday lives when parents’ remote work and children’s remote school were reconciled in homes during the early moments of the COVID-19 pandemic in 2020. The dataset comprises an online survey (n = 92) plus interviews, online diaries, and sampled experiences from 16 Finnish remotely working parents. Identified challenges to the parents’ remote work included interruptions and fragmentation of work tasks, non-optimal work ergonomics, and rescheduling of work times. We present the strategies parents used to create new rhythms and routines, a shared space under the same roof, peace, and privacy for daily work and school, as well as managing multiple simultaneous social roles. Parents’ rich experiences provide insights into the early steps of COVID-19-catalyzed remote work. Thus, the paper offers a reference point for exploring potential development trajectories in the increasingly common hybrid work setting.